(untitled) (Fiep Bulletin - online, 2019)
The context of the academic training of Physical Education professionals in the present time needs to increasinglyproblematize their methodologies in the face of social changes and consequently of the teacher market of action of this area ofknowledge. The investigation of the open conceptions of teaching in the university points to a reflective view at the qualitativelevel of the performance of the academics and the teachers in their daily actions of classroom. The open conceptions include inthe planning a view that allows the students to decide, together with the teacher, a possibility within the degree of openness that is proposed in the physical education class (KUNZ, 2003). The objective of this research was to analyze the methodologydeveloped in the discipline of Research and Educational Practice of Athletics in higher education. It is a qualitative study ofexploratory nature, developed in an undergraduate course in Physical Education degree from a private University of São Luís -Ma. Thirty-six university students participated and as a data collection instrument, a pilot questionnaire was initially used and latera more detailed final questionnaire was applied according to the objectives. The results were related to the description of themethodology applied to the discipline, playfulness as a means of transmitting knowledge of athletics in school and to itscontributions to professional training. It was concluded that the teacher plays a fundamental role in the effectiveness of thestrategies used in his class. To plan their practice closely intertwined with theory allows graduates of the area a greater contactwith the reality of the spaces of professional performance.